Turning a lost reef ecosystem into a national restoration program. Issue 6 (7th August 2022) - McAfee, Dominic; McLeod, Ian M.; Alleway, Heidi K.; Bishop, Melanie J.; Branigan, Simon; Connell, Sean D.; Copeland, Craig; Crawford, Christine M.; Diggles, Ben K.; Fitzsimons, James A.; Gilby, Ben L.; Hamer, Paul; et al.
Abstract: Achieving a sustainable socioecological future now requires large‐scale environmental repair across legislative borders. Yet, enabling large‐scale conservation is complicated by policy‐making processes that are disconnected from socioeconomic interests, multiple sources of knowledge, and differing applications of policy. We considered how a multidisciplinary approach to marine habitat restoration generated the scientific evidence base, community support, and funding needed to begin the restoration of a forgotten, functionally extinct shellfish reef ecosystem. The key actors came together as a multidisciplinary community of researchers, conservation practitioners, recreational fisher communities, and government bodies that collaborated across sectors to rediscover Australia's lost shellfish reefs and communicate the value of its restoration. Actions undertaken to build a case for large‐scale marine restoration included synthesizing current knowledge on Australian shellfish reefs and their historical decline, using this history to tell a compelling story to spark public and political interest, integrating restoration into government policy, and rallying local support through community engagement. Clearly articulating the social, economic, and environmental business case for restoration led to state and national funding for reef restoration to meet diverse sustainability goals (e.g., enhanced biodiversity and fisheries productivity) and socioeconomic goals (e.g., job creation and recreational opportunities). A key lesson learned was the importance of aligning project goals with public and industry interests so that projects could address multiple political obligations. This process culminated in Australia's largest marine restoration initiative and shows that solutions for large‐scale ecosystem repair can rapidly occur when socially valued science acts on political opportunities. Abstract : Article impact statement : Integrating sociopolitical goals and community stewardship into restoration planning builds support to enable large‐scale restoration. Abstract : Transformación de un Ecosistema Arrecifal Perdido en un Programa Nacional de Restauración Resumen: Actualmente se requiere una reparación ambiental a gran escala que atraviese fronteras legislativas para lograr un futuro socio‐ecológico sustentable. Aun así, habilitar la conservación a gran escala es complicado debido a los procesos de elaboración de políticas que están desconectadas de los intereses socio‐económicos, las múltiples fuentes de conocimiento y las diferentes aplicaciones de las políticas. Consideramos cómo una estrategia multidisciplinaria para la restauración de hábitats marinos generó una base de evidencia científica, apoyo comunitario y el financiamiento necesario para así iniciar la restauración de un ecosistema arrecifal de conchas funcionalmente extinto. Los actores clave formaron una comunidad multidisciplinaria de investigadores, practicantes de la conservación, comunidades de pescadores recreativos y órganos gubernamentales que colaboró con varios sectores para redescubrir los arrecifes perdidos de Australia y comunicó el valor de su restauración. Las acciones realizadas para armar el caso para la restauración marina a gran escala incluyeron la síntesis del conocimiento actual sobre los arrecifes de conchas en Australia y su declinación histórica, el uso de esta historia para contar una narración convincente que active el interés público y político, la integración de la restauración a la política gubernamental y la movilización del apoyo local por medio de la participación comunitaria. Claramente, la articulación del caso del negocio social, económico y ambiental para la restauración llevó al financiamiento estatal y nacional para la restauración arrecifal a cumplir diversos objetivos socio‐económicos (p. ej.: creación de empleos, oportunidades recreativas) y de restauración (p. ej.: una productividad realzada de la biodiversidad y las pesquerías). Una lección clave que aprendimos fue lo importante que es alinear los objetivos del proyecto con los intereses públicos y de la industria, de tal manera que los proyectos aborden las múltiples obligaciones políticas. Este proceso culminó con la iniciativa de restauración marina más grande en Australia y demuestra que las soluciones para la reparación de los ecosistemas a gran escala pueden ocurrir rápidamente cuando la ciencia con valor social actúa sobre las oportunidades políticas.